2020
DOI: 10.1002/cam4.2825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic value of circulating tumor cells with CytoSorter® CTC capture system in patients with breast cancer

Abstract: Purpose In this study, we aimed to investigate the viability of utilizing CytoSorter® system to detect circulating tumor cells (CTCs) and to evaluate the diagnostic value of CTCs in breast cancer (BC). Methods A total of 366 females patients suspected of having BC and 30 healthy female volunteers were enrolled in this study. CTCs were enriched by CytoSorter®, a microfluidic‐based CTCs capturing platform. CTC detection was performed before operation or biopsy. Based on the biopsy results, patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 31 publications
(101 reference statements)
9
59
0
Order By: Relevance
“…Previous study with CytoSorter® in BC showed that CTC could re ect tumor burden and could be used as a diagnostic aid in BC screening and early diagnosis [8]. First we compared CTCs with BC patients' clinicopathological features and found that CTCs were associated with tumor stage and tumor size, but not with lymph node metastasis, patients' age and tumor molecular subtype and histology grade.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous study with CytoSorter® in BC showed that CTC could re ect tumor burden and could be used as a diagnostic aid in BC screening and early diagnosis [8]. First we compared CTCs with BC patients' clinicopathological features and found that CTCs were associated with tumor stage and tumor size, but not with lymph node metastasis, patients' age and tumor molecular subtype and histology grade.…”
Section: Discussionmentioning
confidence: 96%
“…CytoSorter ® epithelial cells detection kit was used for CTC enrichment. CTC detection procedure was described as in the previous study [8]. Once the CTC enrichment was nished, the CytoChipNano micro uidic chip was removed from CytoSorter ® and proceed to the immuno uorescence staining of PanCK-FITC, CD45-PE and DAPI.…”
Section: Ctcs Detectionmentioning
confidence: 99%
See 3 more Smart Citations